The Potential of Red Blood Cells in Regenerative Medicine: A Paradigm Shift in Cellular Therapy - Fábio Ramos Costa; Joseph Purita; Ansar Mahmood; Rubens Martins; Bruno Costa; Bruno Lima Rodrigues; Stephany Cares Huber; Gabriel Silva Santos; Luyddy Pires; Gabriel Azzini; André Kruel; José Fábio Lana (Cells)
Red blood cells (RBCs) have traditionally been excluded from orthobiologic formulations due to inflammation, oxidative stress, and hemolysis concerns. However, emerging evidence suggests that RBCs may play an active role in regenerative medicine, contributing to immune modulation, vascular support, and oxidative balance. Their interactions with macrophages, involvement in nitric oxide signaling, and release of extracellular vesicles suggest they may influence tissue repair more than previously assumed. Despite these potential benefits, RBC retention in orthobiologic preparations like platelet-rich plasma (PRP) and bone marrow aspirate concentrate (BMAC) remains controversial, with most protocols favoring their removal in the absence of robust translational clinical data. This review explores the biological functions of RBCs in regenerative medicine, their potential contributions to PRP and BMAC, and the challenges associated with their inclusion. While concerns about hemolysis and inflammation persist, controlled studies are needed to determine whether selective RBC retention could enhance musculoskeletal healing in some scenarios. Future research should focus on optimizing RBC processing techniques and evaluating their impact on clinical applications. Addressing these gaps will clarify whether RBCs represent an overlooked but valuable component in regenerative therapies or their exclusion remains justified.